Comparison of Sensory Observation and Somatosensory Stimulation in Mirror Neurons and the Sensorimotor Network: A Task-Based fMRI Study - Zhou, Zhiqing; Chen, Songmei; Li, Yuanli; Zhao, Jingjun; Li, Guanwu; Chen, Lei; Wu, Yuwei; Zhang, Sicong; Shi, Xiaolong; Chen, Xixi; Xu, Shutian; Ren, Meng; et al. (Frontiers in Neurology, 2022)
Objective: This study aimed to investigate the brain plasticity by somatosensory stimulation (SS) and sensory observation (SO) based on mirror neuron and embodied cognition theory. Action observation therapy has been widely adopted in motor function improvement for post-stroke patients. However, SO therapy is whether effective for sensory recovery in stroke patients or not, which has not been elaborated yet. In the present study, we explored the therapeutic potential of SO for sensorimotor dysfunction and provided new evidence for neurorehabilitation. Methods: Thirty healthy right-handed adults (15 males and 15 females), aged 18-30 (mean = 22.57, SD = 2.49) years were enrolled. All subjects were evaluated with task-based function magnetic resonance imaging (fMRI) to discover the difference in brain activation between SO and SS. We used a block design with 3 conditions viewed during fMRI scanning: watching a sensory video of brushing (task condition A, defined as SO), brushing subjects' right forearm with watching a non-sense string (task condition B, defined as SS) and watching a non-sense string (rest condition). One-sample t-tests were performed to identify brain regions and voxels activated for each task condition. Results: The task-based fMRI have shown that the bilateral postcentral gyrus, left precentral gyrus (PreCG), left supplementary motor area (SMA), right supramarginal gyrus (SMG), bilateral middle temporal gyrus and left thalamus were significantly activated during SS. While in addition to left PreCG, left SMA, right SMG and left thalamus, SO could also activate areas containing mirror neurons, like right PreCG, left inferior parietal gyrus, left insula and left inferior frontal gyrus. Conclusion: SO could activate mirror neurons and sensorimotor network-related brain regions in healthy subjects like SS. Therefore, SO may be a promising novel therapy approach for sensorimotor dysfunction recovery for post-stroke patients. Trial registration: Chinese Clinical Trial Registry, ChiCTR2000040609. Registered on December 03, 2020, http://www.chictr.org.cn/showproj.aspx?proj=65275. Keywords: sensory observation, somatosensory stimulation, mirror neurons, sensorimotor network, functional magnetic resonance imaging